Prevalence and Impact of BRAF mutation in patients with concomitant papillary thyroid carcinoma and Hashimoto’s thyroiditis: a systematic review with meta-analysis - Janicki, Lukasz; Patel, Agastya; Jendrzejewski, Jarosław; Hellmann, Andrzej (Frontiers in Endocrinology, 2023)
Hashimoto thyroiditis (HT) increases the risk of papillary thyroid carcinoma (PTC) development but may also ameliorate its course. The aims of this meta-analysis was to identify incidence of BRAF mutation and its impact on clinicopathological features in patients with concomitant PTC-HT.Medline, Cochrane Library, Scopus, and Web of Science were searched until 16.09.2022, resulting in 227 articles, of which nine studies were included. Summary estimates, comparing patients with (A) BRAF (+) PTC-HT versus BRAF (+) PTC, and (B) BRAF (+) PTC-HT versus BRAF (-) PTC-HT, were generated with Review Manager 5.0. In total, 6395 patients were included in this review. PTC-HT patients had significantly less BRAF mutation than PTC patients (Odds Ratio (OR) (95% Confidence Interval (CI))=0.45 (0.35-0.58), P<0.001). BRAF (+) PTC-HT patients were significantly more likely to have multifocal lesions (OR (95% CI)=1.22 (1.04-1.44), P=0.01) but less likely to have lymph node metastasis (OR (95% CI)=0.65 (0.46-0.91), P=0.01) and extrathyroidal extension (OR (95% CI)=0.55 (0.32-0.96), P=0.03) compared to BRAF (+) PTC patients. BRAF (+) PTC-HT patients were more likely to have multifocality (OR (95% CI)=0.71 (0.53-0.95), P=0.02), lymph node metastasis (OR (95% CI)=0.59 (0.44-0.78), P<0.001) and extrathyroidal extension (OR (95% CI)=0.72 (0.56-0.92), P=0.01) compared to BRAF (-) PTC-HT patients.Evidence suggests that patients with Hashimoto thyroiditis are at significantly higher risk of developing papillary thyroid cancer. However, the course of PTC in patients with both diseases concomitantly has been found to be more indolent than conventional PTC. Additionally, it has been well proven that BRAF mutation results in an aggressive course of PTC. This meta-analysis highlights that the lower incidence of BRAF mutation in patients with PTC-HT than conventional PTC may explain the indolent clinicopathological course in this cohort.